2005
DOI: 10.1136/ard.2004.028191
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M in combination with tumour necrosis factor   induces a chondrocyte membrane associated aggrecanase that is distinct from ADAMTS aggrecanase-1 or -2

Abstract: Objective: To determine whether oncostatin M (OSM) + tumour necrosis factor a (TNFa) induces aggrecanase activity in chondrocyte membranes, to determine the effects of transforming growth factor b1 (TGFb1), interleukin 4 (IL4), and tissue inhibitor of metalloproteinases (TIMPs) on this activity, and to determine whether this activity is due to a known ADAMTS aggrecanase. Methods: Aggrecanase activity and ability of agents to prevent membrane associated aggrecanase activity were assessed by Western blotting. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 63 publications
3
32
1
Order By: Relevance
“…The prodomain of human and mouse ADAMTS-5 contains three potential furin recognition sites (Hurskainen et al, 1999) within a multibasic sequence 258 RRRRR 262 ( Fig. 1) and although the predicted activating cleavage at R 262 263 S is detected in an in vitro expression system (Zeng et al, 2006), activation by cleavage at this site has not been confirmed in vivo.…”
Section: Structural Domains Of Adamts-5mentioning
confidence: 99%
See 3 more Smart Citations
“…The prodomain of human and mouse ADAMTS-5 contains three potential furin recognition sites (Hurskainen et al, 1999) within a multibasic sequence 258 RRRRR 262 ( Fig. 1) and although the predicted activating cleavage at R 262 263 S is detected in an in vitro expression system (Zeng et al, 2006), activation by cleavage at this site has not been confirmed in vivo.…”
Section: Structural Domains Of Adamts-5mentioning
confidence: 99%
“…The disintegrin domain lacks the classical integrin binding sequence (RGD) (Ruoslahti and Pierschbacher, 1986) and does not interact with integrins. The first TS module located C-terminal to the disintegrin domain is highly conserved within the ADAMTS family, including the CSR(T/S)C pentapeptide and conservation of selected glycine, tryptophan and proline residues (Hurskainen et al, 1999). The cysteine rich-region contains ten cysteine residues that are also highly conserved in ADAMTS enzymes.…”
Section: Structural Domains Of Adamts-5mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies investigating arthritis and OA with ADAMTS4/5 knockout mice have revealed that inhibition of ADAMTS5, but not ADAMTS4, mitigates aggrecan degradation and cartilage destruction, suggesting that ADAMTS5 has an important function in aggrecan degradation in mice (20)(21)(22). However, in human chondrocytes, ADAMTS4 is upregulated by interleukin (IL)-1, tumor necrosis factor α, oncostatin M and transforming growth factor β, indicating that ADAMTS4 functions as the primary aggrecanase in human OA cartilage (4,8,9,(23)(24)(25). The results of the present study, with regard to the mRNA expression of ADAMTS4 in human OA chondrocytes under monolayer culture, provide the first indications that OPN selectively inhibits ADAMTS4 expression, while the expression of ADAMTS5 is not affected by OPN.…”
Section: Discussionmentioning
confidence: 81%